Sistem Pendukung Keputusan Pemilihan Wi-Fi Extender dengan Pendekatan Complex Proportional Assessment dan Rank Reciprocal - Nurhasan Nugroho; Fryda Fatmayati; Allan Desi Alexander; Mursalim Tonggiroh (Jurnal Sistem Komputer dan Informatika (JSON), 2023)
A Wi-Fi Extender is a device needed to expand the range and improve the quality of the Wi-Fi signal. To determine the choice, decision makers must know one by one the specifications of the existing products. This results in making decisions difficult and requiring a long time. So the aim of this research is to develop a decision support system for choosing a Wi-Fi Extender using the Rank Reciprocal and COPRAS (Complex Proportional Assessment) weighting approach to make it easier to make decisions in a relatively short time. The Rank Reciprocal approach is used to rank or weight the criteria given by decision makers. Meanwhile, the COPRAS approach is used to obtain the best alternative which is evaluated by calculating the effectiveness index directly proportional to the criteria considered to provide benefits and costs. Based on the case study that was carried out, the highest utility result was obtained, namely the Mercusys MW300RE (A4) which obtained a score of 100. The output produced by the decision support system in the case study that was carried out obtained the same score as manual calculations. Apart from that, the usability testing results obtained an average value of 88.75%. This shows that the system is declared suitable for use because it is in accordance with its function and use.